Domestifikasi Anggrek di Distrik Merauke Kabupaten Merauke–Papua - Helena G. Burok; Rosye H.R. Tanjung; Maklon Warpur (Jurusan Biologi FMIPA Universitas Cenderawasih, 2009)
Inventory study of cultivated orchid in District Merauke, Merauke City was done from March–June 2006. Survey methods was used in this study. There were ten species of orchid in this area, consisted of 8 species of native Papuan orchids (Acriopsis javanica Reinw, Dendrobium anthenatum, Dendrobium diskolour Lind, Dendrobium konkolor Lind, Dendrobium nindii, Dendrobium johanes, and two hibrids), and 2 introduce species (Phalaenopsis sp and Phalaenopis amabilis). Dendrobium anthenatum, Dendrobium diskolour Lind, Dendrobium konkolor Lind, and Dendrobium johanes were the most frequently found species, Dendrobium johanes were mostly encountered on the bark of eucalypt tree on secondary forest wich had high humidity. The problems in orchid cultivation in those area were drought, pest, pathogen, and lack of guidance in orchid cultivation as well. Key words: Inventory, orchid, Merauke District, Merauke City.